Quality Improvement Initiative to Reduce Variability and Improve Stewardship of Antimicrobial Prophylaxis for Transrectal Prostate Needle Biopsy - Recabal, Pedro (World J Urol, 2019)
PURPOSE: To assess the impact of implementing the recommendations included in the 2014 American Urological Association (AUA) white paper on complications of transrectal prostate needle biopsy (PNB). METHODS: In the outpatient setting of a single tertiary-care institution, prophylactic antibiotic use and rate of infectious complications were compared before and after implementation by nursing of a standardized algorithm to select antibiotic prophylaxis (derived from the recommendations of the AUA white paper). The 584 patients in cohort A (January 2011–January 2012) received antimicrobial prophylaxis at the discretion of the treating physician; 654 patients in cohort B (January 2014–January 2015) received standardized risk-adapted antibiotic prophylaxis. Data on antibiotics administered and infectious complications were analyzed. RESULTS: Fluoroquinolone was the most common prophylactic regimen in both cohorts. In cohort A, 73% of men received a single-drug regimen, although 19 different regimens were utilized with duration of 72 hours. In cohort B, 97% received 1 of 4 standardized single-drug antibiotic regimens for duration of 24 hours. Infectious complications occurred in 19 men (3.3%) in cohort A, and in 18 men (2.8%) in cohort B (difference − 0.5%; one-sided 95% CI: 1.1%). No clinically relevant increase in infectious complication rates was found after implementing this quality improvement initiative. CONCLUSIONS: Use of a standardized risk-adapted approach to select antibiotic prophylaxis for PNB by nursing staff reduced the duration of antimicrobial prophylaxis and number of antibiotic regimens used, without increasing the rate of infectious complications. Our findings validate the current AUA recommendations for antibiotic prophylaxis.